(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract : The study of historians’ curricula has a special importance because it shows the stages that historical writing went through throughout the Islamic ages. Therefore, one of the historians who lived at the end of the fourth century AH was selected and died in the middle of the second decade of the fifth century AH. The People of Egypt by Ibn al-Tahan (d.: 416 AH), a systematic study.